2019
DOI: 10.4103/bc.bc_17_19
|View full text |Cite
|
Sign up to set email alerts
|

Cold blood perfusion for selective hypothermia in acute ischemic stroke

Abstract: Hypothermia is the most reliably effective neuroprotectant, and yet systemic complications limit application. A large body of animal data suggests that hypothermia is effective for focal cerebral ischemia, namely acute ischemic stroke. In order to apply hypothermia effectively, a selective approach is required to maximize the effect on the brain while minimizing systemic side effects. Due to poor transferability of promising findings in rodent models to human clinical trials for neuroprotection, the focus of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…Finally, intra-arterial selective cooling, a promising nonpharmacological treatment, can easily be performed shortly after thrombectomy to induce partial hypothermia in the ischemic area. [86][87][88][89] In previous pilot study, intra-arterial selective cooling has been performed in AIS undergoing EVT. [90] Cold 0.9% sodium chloride (4°C) was infused to the ischemic territory before recanalization (10 ml/min for 5 min) through microcatheter and postrevascularization (30 ml/min for 10 min) through the guiding catheter.…”
Section: Following Revascularizationmentioning
confidence: 99%
“…Finally, intra-arterial selective cooling, a promising nonpharmacological treatment, can easily be performed shortly after thrombectomy to induce partial hypothermia in the ischemic area. [86][87][88][89] In previous pilot study, intra-arterial selective cooling has been performed in AIS undergoing EVT. [90] Cold 0.9% sodium chloride (4°C) was infused to the ischemic territory before recanalization (10 ml/min for 5 min) through microcatheter and postrevascularization (30 ml/min for 10 min) through the guiding catheter.…”
Section: Following Revascularizationmentioning
confidence: 99%
“…31 Contemporary studies using specialized catheters have shown the potential for rapid brain cooling. [32][33][34] A mean brain temperature of 26.5°C was achieved in 30 min in a swine acute stroke model with reduction of MRI stroke volumes compared to controls. 34 A study in a canine stroke model showed that brain cooling to 31°C could be achieved in less than 25 min, again with a significant reduction in MRI stroke volumes.…”
Section: Selective Cerebral Thmentioning
confidence: 95%
“…A preliminary specification is necessary. Regarding the therapeutical approach in acute ischemic stroke, there are two main methodological types of cooling/hypothermia interventions: (systemic) hypothermia and local (brain) cooling [93].…”
Section: Systemic Hypothermia (Selective Local Brain) Coolingmentioning
confidence: 99%